Effects of multiscale phase-mixing and interior conductance in the lunar-like pickup ion plasma wake. First results from 3-D hybrid kinetic modeling. (July 2018) - Lipatov, A.S.; Sarantos, M.; Farrell, W.M.; Cooper, J.F.
Abstract: The study of multiscale pickup ion phase-mixing in the lunar plasma wake with a hybrid model is the main subject of our investigation in this paper. Photoionization and charge exchange of protons with the lunar exosphere are the ionization processes included in our model. The computational model includes the self-consistent dynamics of the light ( H + or H 2 + and He + ), and heavy ( Na + ) pickup ions. The electrons are considered as a fluid. The lunar interior is considered as a weakly conducting body. In this paper we considered for the first time the cumulative effect of heavy neutrals in the lunar exosphere (e.g., Al, Ar), an effect which was simulated with one species of Na + but with a tenfold increase in total production rates. We find that various species produce various types of plasma tail in the lunar plasma wake. Specifically, Na + and He + pickup ions form a cycloid-like tail, whereas the H + or H 2 + pickup ions form a tail with a high density core and saw-like periodic structures in the flank region. The length of these structures varies from 1.5 R M to 3.3 R M depending on the value of gyroradius for H + or H 2 + pickup ions. The light pickup ions produce more symmetrical jump in the density and magnetic field at the Mach cone which is mainly controlled by the conductivity of the interior, an effect previously unappreciated. Although other pickup ion species had little effect on the nature of the interaction of the Moon with the solar wind, the global structure of the lunar tail in these simulations appeared quite different when the H 2 + production rate was high.